The Effectiveness of Zakat in Developing Muslims in Malaysia - Khairul Azhar Meerangani (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2019)
Zakat is the third of the five pillars of Islamic faith, relating to wealth and welfare of the society that helps to close the gap between the poor and the rich. The efficient and systematic zakat management is able to propel it’s potential as an instrument of human developments especially among Muslims. The optimum utilization of zakat funds is essential to improving the quality and potential of every Muslim. In Malaysia, zakat is administrated by the Islamic Religious Council (IRC) in every state. The IRC is responsible for determining the beneficiary's qualification and the type of relief that is appropriate based on the background of each recipient so that the relief can be utilized to fulfill their needs. This study aims to assess the potential of zakat in developing the quality of Muslims in Malaysia by highlighting the practice of each IRC in distributing relief to each qualified zakat recipient. The distribution statistics and the form of programs provided by the IRC were analyzed descriptively to see the potential of zakat itself practically in improving the quality of Muslims. The study found that the IRC has provided various programs aimed at improving the quality of asnaf through equitable distribution of economics, social welfare distribution, human capital production and upgrading of education. Thus, every Muslim, especially zakat payers, should take the opportunity to equally engage with the IRC to ensure that zakat funds can be optimized for the developments of Muslims in Malaysia.